Exploration the role of pro-inflammatory fibroblasts and related markers in periodontitis: combing with scRNA-seq and bulk-seq data - Wu, Erli; Gu, Feihan; Zhuo, Qiangqiang; Gao, Ziyang; Zhang, Yu; Li, Jingjing; Yin, Xuan; Bao, Weimin; Zhou, Xianqing; Liang, Feng; Yang, Shouxiang; Wang, Yuanyin; et al. (Frontiers in Immunology, 2025)
BackgroundGingival fibroblasts (GFs), as a critical component of periodontal tissue, play a vital role in processes such as collagen synthesis, wound healing, and tissue repair, thereby maintaining the structural integrity of periodontal tissues. Interestingly, recent studies have revealed that GFs also contribute to the pathophysiology of periodontitis by promoting inflammatory responses. However, its specific molecular mechanism and clinical relevance are still not fully understood.MethodsTo find pro-inflammatory gingival fibroblasts (PIGFs) in periodontitis, a comprehensive analysis of single-cell RNA sequencing (scRNA-seq) data from normal and periodontitis patients was conducted. Then, the role of this celltype in periodontitis was further explored by using cell communication. By merging bulk transcriptome data and employing multiple machine learning algorithms, potential feature genes with PIGFs were further screened, which were verified by qPCR and immunofluorescence staining. Lastly, a cell function test was used to examine the part these genes play in the pathogenesis of periodontitis.ResultsThrough single-cell sequencing analysis, we identified PIGFs which were closely related to the development of periodontitis. Cell communication analysis revealed the specific role of PIGFs in periodontitis. Differential gene analysis, WGCNA, and machine learning algorithms identified two genes (MME and TSPAN11) as potential therapeutic targets for periodontitis. Immune infiltration analysis demonstrated a significant correlation between these genes and the immune response. Functionally, down-regulation of MME and TSPAN11 promoted the proliferation and migration of GFs and significantly inhibited the release of inflammatory cytokines and chemokines.ConclusionThis study identified a subpopulation of GFs closely associated with the inflammatory response through scRNA-seq analysis. These cells may contribute to the progression of periodontitis by interacting with various immune and non-immune cell types. Notably, MME and TSPAN11 were identified as key genes associated with this specific GFs subpopulation that may drive disease progression by exacerbating the inflammatory response, suggesting their potential as therapeutic targets for periodontitis.